2021
DOI: 10.1016/j.medj.2021.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Stable neutralizing antibody levels 6 months after mild and severe COVID-19 episodes

Abstract: Background: Understanding mid-term kinetics of immunity to SARS-CoV-2 is the cornerstone for public health control of the pandemic and vaccine development. However, current evidence is rather based on limited measurements, losing sight of the temporal pattern of these changes. Methods: We conducted a longitudinal analysis on a prospective cohort of COVID-19 patients followed up for >6 months. Neutralizing activity was evaluated using HIV reporter pseudoviruses expressing SARS-CoV-2 S protein. IgG antibody tite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
87
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(110 citation statements)
references
References 29 publications
22
87
1
Order By: Relevance
“…Among 210 Spanish patients, Pradenas et. al showed similar results in a study with a different antibody evolution according to severity of the disease [ 18 ]. They showed a slow decline in antibody level among mild/asymptomatic patients and a two-phase decline among hospitalized patients: fast initial decline, slowing down after 80 days [ 18 ].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Among 210 Spanish patients, Pradenas et. al showed similar results in a study with a different antibody evolution according to severity of the disease [ 18 ]. They showed a slow decline in antibody level among mild/asymptomatic patients and a two-phase decline among hospitalized patients: fast initial decline, slowing down after 80 days [ 18 ].…”
Section: Discussionsupporting
confidence: 56%
“…al showed similar results in a study with a different antibody evolution according to severity of the disease [ 18 ]. They showed a slow decline in antibody level among mild/asymptomatic patients and a two-phase decline among hospitalized patients: fast initial decline, slowing down after 80 days [ 18 ]. Finally, a pre-print prospective study among 308 French patients that have found a half-live of anti-S IgG of 41 weeks, have shown that antibodies persist for longer periods of time in women than in men [ 19 ].…”
Section: Discussionsupporting
confidence: 56%
“…Severe COVID-19 has been related to increased age, high levels of inflammatory markers and seroconversion (Staines et al, 2021). Persistent seroconversion and higher neutralizing titers have been found consistently in hospitalized SARS-CoV-2 infected individuals (Trinité et al, 2021;Pradenas et al, 2021). These studies support the relevance of alternative immune mechanisms to humoral responses crucial in limiting SARS-CoV-2 pathogenesis.…”
Section: Discussionsupporting
confidence: 57%
“…Also, neutralizing antibodies have been shown to predict severity and survival (Garcia-Beltran et al, 2021). However, high neutralizing antibody titers do not positively correlate with less severe clinical outcome (Trinité et al, 2021;Rydyznski Moderbacher et al, 2020). Antiviral CD4+ and CD8+ T-cell responses are key in the natural control of viral infections (Noel et al, 2016;Pereyra et al, 2010;Kiepiela et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [ 40 , 62 , 63 ] have reported significant losses of specific IgG/neutralizing antibodies three to six months following SARS-CoV-2 infection. In contrast, other studies [ 64 , 65 , 66 ] have shown SARS-CoV-2 sero-positivity to be mostly stable up to six months.…”
Section: Virological Properties Of Sars-cov-2mentioning
confidence: 72%